Torque Teno Virus Viral Load as a Marker of Immune Function in Allogeneic Haematopoietic Stem Cell Transplantation Recipients - William Mouton; Anne Conrad; Antonin Bal; Mathilde Boccard; Christophe Malcus; Sophie Ducastelle-Lepretre; Marie Balsat; Fiorenza Barraco; Marie-Virginie Larcher; Gaëlle Fossard; Hélène Labussière-Wallet; Florence Ader; et al. (Viruses, 2020)
Torque teno virus (TTV) has been proposed as a surrogate biomarker of T-cell function in allogeneic–haematopoietic–stem-cell transplantation (allo-HSCT). Conflicting data exists regarding the value of TTV to assess the degree of immunosuppression. The aim of the present study was to investigate the correlation between TTV viral load and immune function. Using samples from a prospective cohort composed of healthy-volunteers (HV) and allo-HSCT recipients at 6 months post-transplantation, we assessed the correlation between TTV viraemia and immune cell counts or T-cell proliferation capacity post-phytohaemagglutinin stimulation. TTV viraemia was detected in 68% of HV (n = 80) and 100% of allo-HSCT recipients (n = 41; p < 0.001); it was significantly higher in allo-HSCT recipients (3.9 vs. 2.1 Log copies/mL, p < 0.001). There was no correlation between T-cell function and CD3+T-cell count (rho: 0.002) suggesting that T-cell count can normalise without full functional recovery. Furthermore, no significant correlation was observed between TTV viraemia and absolute total/subset lymphocyte counts (rho: <0.13). The highest correlation was observed between TTV viral load and T-cell proliferation capacity (rho: −0.39). We therefore report an inverse correlation between T-cell function and TTV viraemia that is independent of T-cell count. Monitoring of TTV viraemia could be a fast suitable option to objectively assess the competence of immune function in at-risk populations.